Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1152/japplphysiol.01282.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin in rVLM mediates electroacupuncture inhibition of cardiovascular reflex excitatory response in rats

Abstract: . Nociceptin in rVLM mediates electroacupuncture inhibition of cardiovascular reflex excitatory response in rats. J Appl Physiol 98: 2056 -2063, 2005. First published January 13, 2005; doi:10.1152/japplphysiol.01282.2004 at Neiguan-Jianshi acupoints through an opioid mechanism inhibits the cardiovascular pressor response induced by mechanical stimulation of the stomach. Because nociceptin also may regulate cardiovascular activity through its action in the brain stem, we hypothesized that this neuromodulator s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 47 publications
5
65
1
Order By: Relevance
“…We microinjected 50 nl of gabazine, kynurenic acid, or saline unilaterally into the NAmb, rVLM, or cVLM. Of note, several of our previous studies (8,19,42) have demonstrated significant blockade of EA's actions following unilateral administration.…”
Section: Chemicalsmentioning
confidence: 78%
See 3 more Smart Citations
“…We microinjected 50 nl of gabazine, kynurenic acid, or saline unilaterally into the NAmb, rVLM, or cVLM. Of note, several of our previous studies (8,19,42) have demonstrated significant blockade of EA's actions following unilateral administration.…”
Section: Chemicalsmentioning
confidence: 78%
“…(8,19,42). In this regard, we have shown that repeated gastric distention induces consistent increases in arterial pressure in normoxic normocapnic rats and that EA modulates these pressor responses (8,12,19,42,48,49). Fewer studies have reported that gastric distention also can reflexly decrease blood pressure (29,39).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…More recently, we have shown that nociceptin and gamma aminobutyric acid (GABA) are involved in inhibition of visceral reflex-induced increases in blood pressure following 30 minutes of low-frequency EA at P5-P6 acupoints, located over the median nerve on the forearms. 19,20 In our experimental models, we have demonstrated that low-frequency (2-4 Hz) but not high-frequency (20-100 Hz) EA effectively stimulates somatic afferents to provide input to regions such as the rVLM that regulate sympathetic outflow. 15,21 Our studies have also examined the concept of point specificity with regard to acupuncture's ability to lower elevated BP.…”
Section: Neural Mechanisms Of Cardiovascular Regulation By Acupuncturmentioning
confidence: 87%